Determination of Pro-BNP and Troponin I Levels for ShortTerm Mortality Prediction in Ischemic Stroke Patients who did not Undergo Revascularization - ÖZPOLAT, ÇİĞDEM; ONUR, ÖZGE ECMEL; DENİZBAŞI ALTINOK, ARZU; AKOĞLU, HALDUN (My University, 2022)
Introduction: Emergency departments (EDs) are the first place to start treatment for most stroke patients. Prognozing patients for planning and proper management of the therapies have an important place in approaching stroke patients. Many studies have been carried out with serum biomarkers especially in terms of prognosis stroke. Our objective, in this study, is to research short-term (14th day) mortality prediction of serum Troponin I (TnI) and pro-brain natriuretic peptide (BNP) levels. Methods: This was a prospective and observational prognostic test study. All consecutive patients admitted to the ED with the onset of symptoms in the past 24 h and diagnosed with the first episode of acute ischemic stroke were included in the study. A total of 121 subjects were included in the study. On admission, pro-BNP and TnI were collected from all subjects. On the 14th day of admission, patients were checked for mortality. Results: Of 121 patients, 14 (11.5%) had a mortal outcome at the end of the 14th day. The overall median pro-BNP level of all patients was 799.00 pg/ml (IQR: 220.00–2818.25). The median pro-BNP level of the non-survivor group was significantly higher than that of the survivor group (p:0.030). However, there was no significant difference between the TnI levels of the mortality groups. The optimal cutoff value of serum pro-BNP levels as an indicator of mortality on the 14th day was estimated to be 509 pg/ml (sensitivity: 85.7%, specificity: 49.5%, and AUC: 0.68 [95% CI, 0.59–0.769]). Discussion and Conclusion: Various biomarkers are investigated for prediction of mortality in ischemic stroke patient. According to our study, elevated pro-BNP values are associated with mortality. Further study with larger patient cohorts can be studied regarding the relationship between these threshold, in terms of predicting the mortality, in a more comprehensive study, as well as using subgroup and underlying conditions.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Ischemic stroke; troponin I; pro-BNP; prognosis